Design and Development of an Automatic T-Shirt Folding Tool Based on the Arduino Uno Microcontroller - Aan Priyadi; Marzuki, Imam; Aprilia, Ira (Universitas Panca Marga, 2022)
One of the household chores that is concerned about this problem is folding the t-shirt from the drying process. When there are lots of stacks of t-shirts, especially for laundry entrepreneurs. Manually folding a t-shirt will certainly look less presentable if done very quickly. The purpose of this study is to accelerate the activity of the laundry entrepreneur, therefore a model of tool that can help in t-shirt folding quickly with a workforce is automatically created. Using six servo motors as a folding drive on the right, left and bottom. To start the process when the tool is used, by utilizing an ultrasonic sensor to start and stop the folding process automatically. The components in this study are controlled by the Arduino UNO microcontroller so that it can work automatically in accordance with the commands that have been applied. There are ten tests using t-shirts of the same size. So the results of the ten testing processes carried out a folding duration of about 3 seconds with 1 t-shirt, 9 seconds by folding 3 t-shirts, 15 seconds by folding 5 t-shirts, 21 seconds by folding 7 t-shirts, and 30 seconds by folding 10 t-shirts. It can be concluded that folding a t-shirt using this tool feels faster and neater than the manual folding process.